Light‐Driven Sustainable Hydrogen Production Utilizing TiO2 Nanostructures: A Review. Issue 1 (5th September 2018) - Cai, Jingsheng; Shen, Jiali; Zhang, Xinnan; Ng, Yun Hau; Huang, Jianying; Guo, Wenxi; Lin, Changjian; Lai, Yuekun
Abstract: As a promising alternative clean energy to fossil fuels, H2 has been given increasing attention, and efficient H2 production is urgently required. Photocatalytic H2 generation from water splitting (WS) is deemed to be a promising and green route for H2 production. TiO2 has been widely utilized in WS owing to the stability, low cost, corrosion resistance, and environmental safety properities. Nevertheless, two dominant defects (inferior absorption performance in visible light and recombination of photogenerated e − –h + pairs) still impede the development of TiO2 . This review offers a comprehensive overview of the progress of various routes for TiO2 nanostructures (0D–3D) and diversified modifications for enhanced H2 production. Further, the perspectives and opportunities for TiO2 based materials are promoted. Persistent efforts are needed to equip the TiO2 nanomaterials with original advanced commercialization and functionality. Abstract : The state‐of‐the‐art development of fabrication methods on 0D, 1D, 2D, and 3D TiO2 nanostructures is reviewed first. Then, some critical engineering strategies to enlarge the active surface area, enhance visible light absorption, and suppress the recombination of electrons/holes that benefit their photo/phtotelectron‐catalytic water splitting activity, are looked into.